A one‐step DNA sequencing strategy to HLA type hematopoietic stem cell donors at recruitment – rethinking typing strategies. Issue 3 (10th February 2013) - Tu, B.; Cha, N.; Yang, R.; Ng, J.; Hurley, C. K.
<x xml:space="preserve">Abstract</x> In order to reduce the time required to identify a match for unrelated donor hematopoietic stem cell transplantation, a one‐step DNA sequencing strategy was employed at the time of recruitment. The impact of this strategy on human leukocyte antigen (HLA) typing resolution and the effect of current registry requirements on resolution and coding of assignments were evaluated. Sanger‐based DNA sequencing was used to obtain diploid exons 2 and 3 HLA‐A, ‐B and ‐C assignments of 2747 unrelated African American and 1822 European American volunteers at recruitment. The results demonstrate the high resolution of the approach and challenge several aspects of the current registry typing strategy. Of the 46% of African American and 74% of European American individuals whose HLA typing resulted in alternative genotypes, the majority (≥93%) was predicted to have only a single 'common' genotype among the alternatives. The common practice of adding secondary assays to resolve alternative genotype assignments that include more than two antigen groups was also evaluated. While the percentage of assignments with greater than two antigen groups reached as high as 21% (HLA‐A in European Americans), only 1.8% of individuals at most carried two common genotypes encompassing three antigen groups. The assignment of (National Marrow Donor Program) NMDP‐designated allele codes to the one‐pass results reduced the resolution substantially and introduced genotypes that were not included in the laboratory's assignments. We suggest the alternative strategy of using the exons 2–3 diploid nucleotide sequence as the assignment submitted to the registry with the added benefit of immortalizing the assignment in time regardless of the introduction of novel alleles. To keep pace with current donor selection criteria and with the increasing number of new alleles, it is time to rethink our recruitment typing strategies.